“There just isn't any other option—so we just have to put up with it”: mental health in women's cycling and the necessity of structural change - Colangelo, Jill; Smith, Alexander; Buadze, Anna; Liebrenz, Michael (Frontiers in Sports and Active Living, 2023)
Historically, bicycle riding connoted freedom, independence, and enhanced mental and physical wellbeing for women. Persevering through criticism and moral panic, female cyclists have been competitive since the late 19th century—many earning substantial prize money and prestige. Unfortunately, this progress was not linear in its trajectory and contemporary professional women's cycling continues to be pervaded by structural and cultural challenges, which can have deleterious effects on athlete mental health. Notably, socioeconomic pressures endure, like unstable employment terms, limited team support, and role conflicts. Furthermore, sexual harassment, body shaming, and manipulation may characterize women's experiences with their coaches and teams. Sizable investment gaps between men's and women's teams and competitions often underpin these scenarios of disadvantage. Alongside hindering the development of women's cycling, these adverse circumstances may induce psychosocial risk factors. Within this context, by highlighting sport-specific and sex-specific considerations, the emerging subdiscipline of sports psychiatry can be valuable for protecting and promoting athlete welfare in women's cycling. Raising awareness about extant symptoms, vulnerabilities, contributing behaviours, and systemic issues, can bolster efforts to develop better conditions and care equivalence. To that end, this perspective article draws upon anecdotal and scholarly evidence to provide an overview of psychiatric concerns in women's professional cycling. This informs recommended strategies to improve mental health and advance equality within the sport, which should involve actions from several stakeholders, such as athletes, teams, and governing bodies.